2020
DOI: 10.18203/2349-2902.isj20201399
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of early laparoscopic cholecystectomy versus delayed laparoscopic cholecystectomy for patients with acute cholecystitis

Abstract: Background: This prospective randomized study was undertaken to to assess the outcomes of early versus delayed cholecystectomy for patient’s acute cholecystitis.Methods: 70 patients with acute cholecystitis were prospectively randomized to either an early laparoscopic cholecystectomy (n=35) or a delayed laparoscopic cholecystectomy group (n=35). The mean operative time, conversion rate, total hospital stay, intra-operative and post-operative complications, average hospital cost were evaluated between the two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Some studies show the difference to be smaller (around 2–4 days) ( 63 , 74 , 85 , 88 – 91 ), but all studies looking at length of stay found it shorter for early procedures ( 52 , 64 , 76 , 84 , 92 94 ), even when comparing open cholecystectomy approaches ( 95 ).…”
Section: Why Early Cholecystectomy Is Importantmentioning
confidence: 99%
“…Some studies show the difference to be smaller (around 2–4 days) ( 63 , 74 , 85 , 88 – 91 ), but all studies looking at length of stay found it shorter for early procedures ( 52 , 64 , 76 , 84 , 92 94 ), even when comparing open cholecystectomy approaches ( 95 ).…”
Section: Why Early Cholecystectomy Is Importantmentioning
confidence: 99%
“…Laparoscopic cholecystectomy has been the procedure of choice for symptomatic gall bladder disease [1]. The incidence of gall stones is 10-15% and the lifetime recurrence rate of symptoms or complications in such patients is about 35% [2].…”
Section: Introductionmentioning
confidence: 99%